Perlindungan Hukum Wajib Pajak Dalam Prespektif Asas Kepastian Hukum - Panji Purnomo; Maya Olivia; Ayu Tri Lestari (Cattleya Darmaya Fortuna, 2026)
This study examines taxpayer legal protection from the perspective of the principle of legal certainty in Indonesia, focusing on the integration of norms, practical application by tax authorities, and tax dispute resolution. The study employs a normative legal approach (doctrinal legal research) with a descriptive-analytical method, examining legislation, jurisprudence, and scientific literature as primary and secondary data sources. The analysis is conducted through legislative, case, and conceptual approaches to examine the extent to which taxpayer legal protection aligns with the need for legal certainty and justice in the tax system. The results show that, although legal frameworks such as the 1945 Constitution, the General Provisions and Tax Procedures Law, and their implementing regulations normatively guarantee legal protection and certainty, in practice, there is still unclear formulation of regulations, sudden policy changes, and inconsistent interpretations by tax authorities. This results in uncertainty about obligations, disparities in the treatment of similar taxpayers, and difficulties in utilizing complaint and objection mechanisms. Therefore, this study recommends normative and institutional improvements, such as simplifying and sharpening regulations, increasing policy transparency, and strengthening the independence and quality of tax courts, so that legal protection for taxpayers is truly upheld based on the principles of legal certainty, justice, and citizens' human rights.